Effect of Chromium Ion on the Strength Characteristics and Damage Law of Red Clay - Yu Song; Mingzhi Zhang; Hui Li; Yue Yang; Xuejun Chen; Jun Li (Geofluids)
As heavy metals invade the soil, they will continue to corrode the internal structure of the soil, expand the pores of the internal soil, and destroy the internal skeleton structure of the soil. The shear strength of the soil is reduced and the structure is damaged, causing the building to crack and deform. This research is aimed at analyzing the mechanical strength characteristics and damage discipline of red clay polluted by chromium ions. Taking Guilin red clay as the research object, the chromium pollution concentrations of 0%, 0.01%, 0.05%, and 0.1% contaminated soil were artificially configured indoors to conduct unconsolidated and undrained triaxial tests. The results reveal that chromium ions can destroy the original structure of the red clay. With the increase of chromium ion concentration, the deviatoric stress of red clay decreases. The downward trend is in the form of an exponential function. The deviator stress of red clay contaminated by a low concentration of chromium ions has a significantly decreasing trend. With the increase of the concentration, the deviator stress of red clay tends to decrease. Compared with unpolluted red clay, the contaminated red clay requires less axial pressure to produce the same deformation. The chromium ions in the polluted red clay increase the concentration of ions in the electrical double-layer structure of the soil particles and reduce the stiffness of the soil.